The importance of the internal auditor's roles in establishing and achieving ecotourism - Zainol Abidin, Azlan; Mohd Shariff, Nurhazani (Universiti Utara Malaysia, 2006)
In 1992, the Ecotourism Society defined the term 'ecotourism' as a purposeful travel to natural areas to understand the cultural and natural history of the environment, taking care not to alter the integrity of the ecosystem, while producing economic opportunities that make the conservation of natural resources financially beneficial to local citizens.In order establish and achieve ecotourism, the policy makers and planners in the organizations must work with the knowledge that tourism can have negative impacts on the environment.How can we be assured that organizations have followed all the regulations and policies regarding ecotourism? What can we do to make sure that organizations have taken all the requirements needed for establishing and achieving ecotourism? These questions lead to the understanding of the roles played by the internal auditor in order to help the organizations accomplish their objectives by bringing a systematic, disciplined approach to evaluate and improve effectiveness of risk management, control and governance process.Managers are often removed from the operations for which they are' responsible.Thus, they need assistance to evaluate the adequacy and the effectiveness of the controls they installed or to develop controls that are missing.In accordance, the internal auditors are turned to for these evaluations.This article will outline the importance of their roles in establishing and achieving ecotourism.It will also highlight the roles of the internal auditor before, during and after the ecotourism development.